Diabetic nephropathy: clinical presentation, course, and novel treatment possibilities - Lezaic, Visnja D (General Practice, 2022)
Diabetic kidney disease (DBD) is one of the major complications of diabetes (DM) and the leading cause of chronic kidney disease (CKD) worldwide. About 10% of patients with DBD progress to terminal HBB, and the rest die mostly due to cardiovascular disorders and infection even before they need treatment for kidney replacement. The main strategies to prevent the development and alleviate the progression of DBB in recent decades have been intensive glycemic control and blockade of the renin-angiotensin-aldosterone system. However, this approach did not achieve optimal results. Taking into account the increase in patients with DBB, high spending from the health care budget and the development of new therapeutic possibilities with significant kidney protection, the International Society of Nephrology issued in 2020. (Kidney Disease: Improving Global Outcomes (KDIGO) Guideline) is the first guide to treating patients with DBB. This review paper aims to point out phenotypic variability and present recent advances in the treatment of DBB
Keywords: diabetic kidney disease, KDIGO guide, phenotypic variations, treatment